1977
DOI: 10.1017/s0079497x00010343
|View full text |Cite
|
Sign up to set email alerts
|

A Reappraisal of the Clacton Spearpoint

Abstract: The wooden artifact widely known as the Clacton Spear (pl. 1) was discovered by Samuel Hazzledine Warren, F.G.S., in 1911. He dug it out of an undisturbed part of the freshwater sediments, probably a peaty seam, exposed on the foreshore at Clacton-on-Sea, c. 80 km ENE of London (Warren 1911; 1914, and in conversation with K.P.O. 1933). On 30th September 1911, Warren conducted a party of members of the Essex Field Club on a visit to see the outcrop of Pleistocene fluviatile deposits on the shore west of Clacton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
85
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(87 citation statements)
references
References 10 publications
(8 reference statements)
0
85
0
2
Order By: Relevance
“…There are several notable exceptions that demonstrate that plant remains can survive in a wide variety of contexts. For example, preserved wooden spears are known from the Lower Paleolithic site of Schö ningen, Germany (c. 400 kya, Thieme, 1997), the Middle Paleolithic site of Lehringen in Germany (c. 110-130 kya, Movius, 1950) and the Middle Pleistocene site of Clacton-on-Sea, England (c. 350 kya, Oakley et al, 1977). A variety of wooden artefacts were preserved in a water-logged context at the Middle Pleistocene Acheulean site of Kalambo Falls, Zambia (Clark, 1974).…”
mentioning
confidence: 99%
“…There are several notable exceptions that demonstrate that plant remains can survive in a wide variety of contexts. For example, preserved wooden spears are known from the Lower Paleolithic site of Schö ningen, Germany (c. 400 kya, Thieme, 1997), the Middle Paleolithic site of Lehringen in Germany (c. 110-130 kya, Movius, 1950) and the Middle Pleistocene site of Clacton-on-Sea, England (c. 350 kya, Oakley et al, 1977). A variety of wooden artefacts were preserved in a water-logged context at the Middle Pleistocene Acheulean site of Kalambo Falls, Zambia (Clark, 1974).…”
mentioning
confidence: 99%
“…While it could not be confirmed that it had been hardened in a fire, microscopic analyses showed that it had been carefully shaped (Oakley et al 1977). The artefact was broken, and at 33 cm in length, had many interpretations.…”
Section: The Early Human Occupation Of Britain Early Hominin Occupatimentioning
confidence: 99%
“…In fact, of all of the uses of fire seen among modern huntergatherers, the only one that can be ruled out, at least on the basis of data presently available, is its use for heat-treating flint, though it is also most likely that grease rendering and hide smoking were not practiced as well. While fire may have been used as a source of light, Neandertal cave occupations are almost universally situated at or very near the cave mouth (as is the case with Pech de l'Azé IV and enough wooden implements have been discovered that their use is reasonably demonstrated (Carbonell and Castro-Curel 1992;Freeman et al 1981;Howell 1966;Movius 1950;Oakley et al 1977;Rolland 1999;Thieme 1999;Villa and Lenoir 2006). However, the use of fire to shape or harden such items has not as yet been conclusively demonstrated for any of these finds.…”
Section: How Important Was Fire To Western European Neandertals?mentioning
confidence: 99%
“…They may also be ringed with cobbles to contain the fire and its heat, although this appears to be a rare practice in the Middle Paleolithic. Such hearths are associated with a number of common applications, including modifying raw materials such as wood (Fessler 2006;Gould 1971;Hayden 1981;Mallol et al 2007;Marlowe 2005;Oakley et al 1977;O'Connell 1987) or in heat treatment of lithic raw materials to enhance their flaking qualities (Brown et al 2009;Domanski and Webb 1992). Small hearths also are used to ward off predators (Fessler 2006;Marlowe 2005;Worthman and Melby 2002), to keep irritating (or dangerous) insects at bay (Fessler 2006;Hayden 1981), to fumigate against small rodents (Worthman and Melby 2002), or simply as a means of eliminating site refuse (see Galanidou 2000).…”
Section: Introductionmentioning
confidence: 99%